Female Toddler Presenting with Suspected Gaucher Disease: A Rare Case Report - Yunanto, David; Prihatni, Delita (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Gaucher disease is a rare metabolism disease caused by a mutation of the glucocerebrosidase (GBA1) gene. The mutation causes an accumulation of glucocerebroside lipids (glycolipid glucocerebroside), which are harmful to the body. The accumulation goes within all areas of the body especially within the marrow, liver, and spleen. In the non-Jewish population, Gaucher disease affects 1 out of every 100,000 people. This case report describes the laboratory approach and interpretation of Gaucher disease. A 20-month-old female toddler with an enlarged abdomen accompanied by a history of severe dehydration and seizure without evidence of vomiting and diarrhea came to the nutrition Outpatient Clinic. Physical examination found hepatomegaly of 10 cm under arcus costa and spleen Schuffner 3. Laboratory findings are as follows:  hemoglobin 10.2 g/dL (10.5-13.5 g/dL) and thrombocyte 73,000/mm3 (150,000-450,000/mm3), total bilirubin 1.289 mg/dL (0.100-1.000 mg/dL), direct bilirubin 0.567 mg/dL (0.100-0.300 mg/dL), ferritin 310.1 ng/mL (4.63-204 ng/mL), APTT 41.30 s (21-41 s), CMV IgG and IgM 747.4 AU/mL (<6.0 AU/mL) and 1.3 index (<0.85 index), respectively. Gaucher disease should be considered in patients with unexplained splenomegaly, thrombocytopenia, frequent nosebleeds, anemia, acute or chronic bone pain, and/or delayed development. Gaucher cells shown in bone marrow examination can help diagnose Gaucher disease although the gold standard is the glucocerebrosidase enzyme test. This case report highlights the examination flow until the patient can be diagnosed with LSD in this case Gaucher disease.